Follow Dual Profession : Practitioner Business and College Lecturer - Eka Wahyu Kasih; Ruslaini Ruslaiini; Selvi Agustina (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
Phenomenon profession double as practitioners business at a time lecturer college tall the more come to the fore along increasing demands relevance education tall to dynamics of the business and industrial world . Universities tall need lecturers who do not only control theory , but also has experience practical for learning more contextual and applicable . On the other hand , practitioners business looking at the academic world as room devotion intellectual at a time means actualization professional . This article aim For study profession double from perspective career , ethics , honor , devotion , and welfare term long . Writing article This use method study conceptual – reflective based on experience professional authors and reviewers literature scientific , regulatory education high , and policy related profession lecturer . Approach This used For integrate dimensions normative , practical , and strategic in understand profession double in a way intact . Study results show that profession double can become road meaningful career if executed in a way ethical and professional . Profession This allows integration experience business to in learning , strengthening legitimacy academic , as well as build honor social as figure public . In addition , the profession double also gives structure greater well- being stable through diversification source income and financial strategy term long , at the same time become vehicle devotion through the transfer of knowledge , values and experience to students and society